International comparison method of absolute gravimeter - Jinyang Feng; Shuqing Wu; Chunjian Li; Qiyu Wang; Lishuang Mou; Duowu Su (地球与行星物理论评, 2022)
Gravitational acceleration metrology is the primary means to ensure the international mutual recognition and uniformity of gravity measurement activities, and guarantees the traceability and accuracy of gravity measurement results. Absolute gravimeters are taken as the main tool and carrier for the traceability and transmission of the gravity acceleration value. It can be used as a standard for periodic calibration of the relative gravimeters, as a "ruler" for land, ocean, aviation, and satellite gravity measurement. The National Institute of Metrology (China) has held the First International Comparison in Asia Pacific Regional and the 10th International Comparison of Absolute Gravimeters (ICAG-2017). Based on the former experiences, this paper introduces the preparation, organization and evaluation method of all international comparison measurements. Firstly, the site selection of comparison, observation of vertical gravity gradient, and tidal model before the comparison is introduced. During the comparison, the measurements for the diffraction beam correction and the arrangement of measurement sites were demonstrated. Then, the raw comparison measurements were transferred to the same heights and time, and performed based on the given observation model and constraint equation. After pre-processing, the evaluation of the instrument uncertainty was verified through a compliance test, the degree of instrument equivalence (DoE) and short-term reproducibility were calculated. By analyzing previous comparison results, this paper discusses the significance of international comparison in improving the accuracy of observation data in geophysical research and application, and puts forward some problems faced in the current stage.